INTEGRATION OF GENERAL TECHNICAL KNOWLEDGE IN PROFESSIONAL TEACHING OF TECHNOLOGY TEACHERS - Orshanski, Leonid; Nyshchak, Ivan; Pantiuk, Tetiana; Milyaeva, Valeriya; Matvisіv, Jaroslav (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The content filling of the educational field of «Technology» provides a deeper acquaintance of students with the modern achievements of technology, mastering the practice of design and technological activities. Bearing this in mind, it is topical to develop the scientific principles of engineering training for future teachers of labor training and technology, which led to theoretical substantiation and practical implementation of structural changes in curricula in general technical disciplines. The analysis of the scientific literature and practical experience shows that the proposed structure of the content of the integrated course «Engineering Mechanics» is aimed primarily at intensifying the students’ cognitive activity, as well as their broad involvement in independent work on the design and construction of technical objects. Such circumstances favor direct impact on the content of engineering training of future teachers of labor training and technology linked to the global change in scientific approaches and innovative processes in the creation of technical facilities and also indirect – caused by the development of modern production and information technologies.The article analyzes the current system of engineering training of future teachers of labor training and technology which is characterized by the reorientation of the educational process to the project-technological activity of students. The authors substantiate the necessity of integration of knowledge from the cycle of general technical disciplines in the content of engineering training of future teachers. Based on the didactic principle of continuity and taking into account the requirements of school curricula and cross-curricular relations with different disciplines of vocational training of teachers of labor training and technology, the authors propose the structure and content of the integrated course «Engineering Mechanics», which consists of the following sections: 1) «Statics, kinematics and dynamics»; 2) «Material resistance and machine parts calculation».